The Role of Breakfast and Quality Sleep in Supporting Students' Learning Concentration - Adelia Falih; Hamidah Hamidah; Dadang Herdiansyah; Aning Subiyatin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Students' concentration during learning can have a significant impact both in the present and in the future. Poor concentration can lead to memory issues, suboptimal learning outcomes, and if not properly addressed, can result in long-term consequences, such as a decline in the quality of human resources. The objective is to identify the relationship between students' learning concentration and nutritional status, breakfast habits, and sleep quality. Quantitative research using a cross-sectional design, on 53 elementary school students. A questionnaire was employed to measure the variables of breakfast habits and sleep quality. Anthropometric measurements were based on Z-scores according to Body Mass Index (BMI), adjusted for the students' gender and age, to assess nutritional status. Statistical analysis was conducted using the Chi-square test. A total of 78.2% of students had good concentration, 81.8% had good nutritional status, 69.1% regularly ate breakfast, and 40% had good sleep quality. A significant relationship was found between breakfast habits (p=0.011) and sleep quality (p=0.008). However, no significant relationship was found between nutritional status and concentration (p=0.096). There is a significant relationship between breakfast habits and sleep quality, indicating the importance of educating students and parents on these topics. Although no significant relationship was found between nutritional status and concentration, monitoring and supporting students' nutritional status should continue, with collaboration from health institutions such as local health centers (Puskesmas).